Autophagy in Plants: Both a Puppet and a Puppet Master of Sugars - Janse van Rensburg, Henry Christopher; Van den Ende, Wim; Signorelli, Santiago (Frontiers in Plant Science, 2019)
Autophagy is a major pathway that recycles cellular components in eukaryotic cells both under stressed and non-stressed conditions. Sugars participate both metabolically and as signalling molecules in development and response to various environmental and nutritional conditions. It is therefore essential to maintain metabolic homeostasis of sugars during non-stressed conditions in cells, not only to provide energy, but also to ensure effective signalling when exposed to stress. In both plants and animals, autophagy is activated by the energy sensor SnRK1/AMPK and inhibited by TOR kinase. SnRK1/AMPK and TOR kinases are both important regulators of cellular metabolism and are controlled to a large extent by the availability of sugars and sugar-phosphates in plants whereas in animals AMP/ATP indirectly translate sugar status. In plants, during nutrient and sugar deficiency, SnRK1 is activated, and TOR is inhibited to allow activation of autophagy which in turn recycles cellular components in an attempt to provide stress relief. Autophagy is thus indirectly regulated by the nutrient/sugar status of cells, but also regulates the level of nutrients/sugars by recycling cellular components. In both plants and animals sugars such as trehalose (Tre) induce autophagy and in animals this is independent of the TOR pathway. The glucose-activated G-protein signalling pathway has also been demonstrated to activate autophagy, although the exact mechanism is not completely clear. This mini-review will focus on the interplay between sugar signalling and autophagy.